Characterization of hydrolytic activity of raw starch-digesting amylase (RSDA) from Saccharomycopsis bubodii 2066 on sago (Metroxylon sagu Rottb.) starch - Caubalejo, Rey Jacutin (2011)
A raw starch digesting amylase (RSDA) was purified from Saccharomycopsis bubodii 2066 which was isolated from Philippine Bubod starter. The free enzyme (dialysate) had a specific activity of 3.91U mg-1. It was immobilized by encapsulation with calcium alginate. Specific activity of the immobilized enzyme decreased to 0.26 U mg-1. Hydrolitic activity was evaluated through degree and rate of hydrolysis by determining reducing sugar content as a function of time. The reaction mixtures contained 0.11 mg protein and 0.7 mg protein, for the free and immobilized enzymes, respectively. Degree of hydrolysis using free and immobilized enzyme was 0.11 and 0.03 mg reducing sugar mg-1 protein, respectively. Adsorbability onto raw sago starch was not observed in immobilized enzyme which explains the negative results. On the contrary, the free enzyme almost adsorbed completely. Operational stability in immobilized enzyme was assessed through binding efficiency and enzyme reusability. Binding efficiency was 70.75% efficiency. After reusing the bead for 4 cycles. it retained 18.24% of the original activity.